Komika v díle Karla Poláčka - Nováková, Šárka; Kudrnáč, Jiří, 1953-; Masarykova univerzita. Ústav české literatury a knihovnictví (2006)
Tato diplomová práce se zabývá komikou v díle Karla Poláčka. V úvodních kapitolách jsou rozebrány jednotlivé teorie komiky v různých pracích - Smích od Henriho Bergsona, Teorie komiky od Vladimíra Boreckého, Slovník literární teorie, Poetický slovník od Tibora Žilky. Následuje teoretický základ práce a jednotlivé analýzy Poláčkových knih - Povídky pana Kočkodana, Hedvika a Ludvík, Bylo nás pět a Okresní město. Analýzy se týkají komiky a jejích tří složek - komika charakterová, situační a jazyková. V závěru práce jsou shrnuty všechny poznatky a je ukázána specifičnost komiky Karla Poláčka. Základem je detailní propracování a prolínání všech složek komiky.
This thesis deals with comic at work of Karel Poláček. The opening chapters describe of individually theoris of comic in different novels - The Laughter written by henri Bergson, The Theory of comic written by Vladimír bOrecký, The Dictionary of literary theory, The Poetic dictionary written by Tibor Žilka. Following chapter is about a theoretical pricipl of work and single analyses of Poláček's books - The Stories of Mr. Kočkodan, Hedvika and Ludvík, We were five of friends and The district town. The analyses concern of comics and their three parts - the comic of situation and language, the character comic. At the finish of work are summary all pieces of knowledge and there is shown specific comic of Karel Poláček and there is shown that the basis of this comic is detail work out elaborate and penetration of all parts comic.
Vedoucí práce: Jiří Kudrnáč.
Diplomová práce (Mgr.)--Masarykova univerzita, Filozofická fakulta, 2006.
Keywords: diplomové práce